Analysis of the Influence of Income, Financial Literacy, and Payment Ability on Compliance of BPJS Kesehatan Non-Wage Recipient (PBPU) Contribution Payments in Indonesia - Rizky Basir Batubara; Aqwa Naser Daulay Daulay; Muhammad Ikhsan Harahap (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
This study investigates the effects of income, financial literacy, and payment capacity on the compliance of Non-Wage Recipient (PBPU) members in paying their BPJS Kesehatan contributions. An associative quantitative research design was employed to examine the relationships among the proposed variables. The study involved 98 PBPU participants registered under the BPJS Kesehatan Sibolga Branch Office, who were selected using a simple random sampling technique. The analysis was based on both primary data collected directly from respondents and secondary data obtained from supporting documents. Data were gathered through a structured Likert-scale questionnaire and documentation, then processed using multiple linear regression analysis with SPSS. Before testing the hypotheses, the research instrument was assessed for validity and reliability, while the regression model was evaluated through classical assumption tests, including normality, multicollinearity, and heteroscedasticity. The empirical findings indicate that income, financial literacy, and payment capacity collectively have a significant influence on contribution payment compliance. When examined individually, income and financial literacy demonstrate positive and statistically significant effects on compliance, whereas payment capacity does not show a significant relationship. In addition, the coefficient of determination (R²) of 0.875 suggests that 87.5% of the variation in payment compliance can be explained by the variables incorporated in the research model, while the remaining 12.5% is attributable to other factors beyond the scope of this study. These results highlight the importance of economic conditions and financial literacy as key determinants of contribution payment compliance among PBPU members and provide valuable evidence for designing policies aimed at strengthening the long-term sustainability of Indonesia's National Health Insurance program.